2020
DOI: 10.3390/ijerph17124486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stoffenmanager and a New Exposure Model for Estimating Occupational Exposure to Styrene in the Fiberglass Reinforced Plastics Lamination Process

Abstract: This study aims to evaluate occupational exposure models by comparing model estimations of Stoffenmanager, version 8.2, and exposure scores calculated using a new exposure model with personal exposure measurements for styrene used in the fiberglass-reinforced plastic (FRP) lamination processes in Korea. Using the collected exposure measurements (n = 160) with detailed contextual information about the type of process, working conditions, local exhaust ventilation, respiratory protections, and task descriptions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(52 reference statements)
0
5
0
Order By: Relevance
“…This showed that the multipliers do not explain the exposure very well ( Savic et al , 2017a ). Residual analysis shows that STOFFENMANAGER ® and ART have a systematic tendency to overestimate low exposures and underestimate high exposures ( Mc Donnell et al , 2011 ; Landberg et al , 2017 ; Savic et al , 2017a ; Lee et al, 2019a , b , 2020 ). The reason for this trend is not known.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This showed that the multipliers do not explain the exposure very well ( Savic et al , 2017a ). Residual analysis shows that STOFFENMANAGER ® and ART have a systematic tendency to overestimate low exposures and underestimate high exposures ( Mc Donnell et al , 2011 ; Landberg et al , 2017 ; Savic et al , 2017a ; Lee et al, 2019a , b , 2020 ). The reason for this trend is not known.…”
Section: Discussionmentioning
confidence: 98%
“…The models fail to estimate reasonable worst-case exposure estimates usually by two or more orders of magnitude. Because of this high uncertainty, the exposure is often underestimated in over 10% of the predicted exposures even when using the upper level of the 90 or 95% confidence interval of the 90th or 95th percentile ( Landberg et al, 2015 , 2017 ; Riedmann et al , 2015 ; Savic et al , 2017a ; van Tongeren et al , 2017 ; Lee et al, 2019a , b , 2020 ). The STOFFENMANAGER ® evaluation report by Dutch Ministry of Social Affairs and Employment is not accessible according to personal communication with Cosanta, ECHA, The Finnish Safety and Chemicals Agency, and Rijksoverheid (the Netherlands).…”
Section: Discussionmentioning
confidence: 99%
“…To more objectively assess the possibility of benzene exposure, a scoring system using exposure-related parameters was used. The scoring technique is used to qualitatively or semiquantitatively evaluate the hazard and exposure of chemicals [ [24] , [25] , [26] ]. All 22 patent documents that recorded the use of benzene were evaluated with more than 6 points ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…For Stoffenmanager ® , 11 studies were evaluated (see Table S3) in which spraying activities were included. A main conclusion of most studies is that Stoffenmanager ® is a balanced model with a medium level of conservatism, when considering the 90th percentile [58,78,79]. The few studies that examined the 50th percentile came to a similar conclusion.…”
Section: Information On External Evaluation Of the Models-inhalation ...mentioning
confidence: 93%